Penentuan Geometri Jalan Akses Berdasarkan Aashto dan Kepmen 1827 di Pit A4 Benaung PT.Energi Cahaya Industritama - Arya Mu’min Wally; Tommy Trides; Agus Winarno; Harjuni Hasan; Revia Oktaviani (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Mining roads are one of the most important facilities that greatly affect the smoothness of production and affect mining costs. Therefore, the construction of mining roads must be carried out carefully to meet technical and work safety standards. Road conditions, distance, road slope and road carrying capacity will greatly affect the production capacity of heavy equipment, especially the production capacity of transport equipment. The location of this research is at PT. Energi Cahaya Industritama, precisely in Palaran sub-district, Samarinda city, East Kalimantan province. After observations were made at the research location, it was found that the geometric conditions of the road did not comply with the standards based on the overburden transport equipment or the largest transport equipment, for example, the width of the road on bends and the slope of the road. After conducting the research, the results of the data from the geometry of the access road were obtained, namely, the actual condition of the geometry of the access road on the straight road width is divided into 6 segments with a width of 13.3 meters, 14.3 meters, 14.5 meters, 13.2 meters, 15 meters, 15.7 meters. Meanwhile, the width of the bend road is also divided into 2 segments with a width of 15.9 meters and 15.5 meters respectively. And on the slope of the road there are 2 segments with values ​​of 11.1% and 14.8% respectively. Based on the results of the simulation software, the productivity of the transport equipment was obtained at 92.42 BCM/hour, which shows that productivity has increased by 12.23 BCM/hour from the actual productivity value of 80.109 BCM/hour. It has an average cycle time of 10.33 minutes, which shows a reduction in time or 6.01 minutes faster than the actual average cycle time of 16.34 minutes.